Corrosion-resistant high-strength steel wire rope core and preparation method thereof
By using composite structures such as ultra-high molecular weight polyethylene fiber filaments, steel wire and sisal fiber filaments in the wire rope core, and adding a water barrier layer and a high-strength protective layer, the problem of wire ropes being easily corroded in harsh environments is solved, achieving higher corrosion resistance and service life.
Patent Information
- Application Number
- CN202411928398.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing wire rope cores are prone to corrosion in harsh environments, resulting in reduced performance of wire ropes and pose safety hazards.
The structural design is adopted including a central wire, a secondary outer wire and an outer wire. The central wire is composed of ultra-high molecular weight polyethylene fiber filaments. The secondary outer wire is a steel wire, and the outer wire is a composite material of sisal fiber filaments and nylon fiber filaments. A water barrier layer and a high-strength protective layer are provided on the outer layer.
It improves the comprehensive performance of the rope core, enhances corrosion resistance and high strength, extends the service life of the wire rope, and improves production safety.
Smart Images

Figure CN119711224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel wire rope cores, and in particular to a corrosion-resistant high-strength steel wire rope core and a preparation method thereof. Background Art
[0002] Steel wire rope is made by twisting steel wires with specific geometric dimensions and mechanical properties according to certain rules. It has a spiral structure and is generally composed of a rope core, strands and grease. Steel wire rope has the advantages of high strength, light weight, stability and reliability. It is widely used in construction, mining, metallurgy, petroleum, marine transportation, machinery and other fields. It can be used in elevators, aircraft arresting cables, cranes and other important parts.
[0003] The core of the wire rope has the following functions: 1. Enhance the bearing capacity of the wire rope: The core of the wire rope can bear part of the tension of the wire rope, thereby reducing the load of the wire rope and enhancing the bearing capacity of the wire rope. 2. Stabilize the curvature of the wire rope: The core of the wire rope can stabilize the curvature of the wire rope, reduce the risk of deformation of the wire rope, and thus increase the service life of the wire rope. At present, the commonly used wire rope cores on the market are steel wire rope cores and synthetic material rope cores. The steel wire rope core has high strength and strong tensile and compressive resistance, but it has high density and cannot withstand severe impact and vibration. It is also easily corroded. The synthetic material rope core is light in weight, low in density, high in tensile strength, and has excellent anti-corrosion, acid and alkali resistance. It can withstand large impact and vibration and has a long service life. Relatively speaking, the synthetic material rope core is softer and lacks support for the wire rope strands. As the use of wire ropes becomes more and more widespread, the use scenarios are diverse, and some wire rope use scenarios are also very harsh, such as high temperature and humid environment. Extreme use environments will make the inside of the wire rope susceptible to corrosion, especially the rope core as the core part. Once corrosion occurs, it is easy to cause the performance of the wire rope to drop sharply, which is easy to bring safety hazards. In this regard, a corrosion-resistant high-strength steel wire rope core is proposed to improve the comprehensive performance of the rope core, which is of great significance to extend the overall service life of the wire rope and improve production safety. Summary of the invention
[0004] The object of the present invention is to provide a corrosion-resistant high-strength steel wire rope core to solve the above-mentioned technical problems.
[0005] The present invention provides a corrosion-resistant high-strength steel wire rope core, comprising a central wire, a secondary outer layer wire and an outer layer wire, wherein the secondary outer layer wire is spirally wrapped and twisted around the central wire, and the outer layer wire is spirally wrapped and twisted around the secondary outer layer wire. The central wire comprises a plurality of ultra-high molecular weight polyethylene fiber filaments, the secondary outer layer wire comprises a plurality of steel wires, and the outer layer wire comprises a plurality of sisal wires and a plurality of nylon fiber wires, wherein the quantity ratio of the sisal wires to the nylon fiber wires is 1:1. A water-blocking layer and a high-strength protective layer are sequentially arranged on the periphery of the outer layer wire, wherein the high-strength protective layer comprises a rubber layer and a mixed fiber cloth layer arranged in the rubber layer, wherein the mixed fiber cloth layer is formed by stacking two mixed fiber cloths. The mixed fiber cloth is obtained by twice impregnating an aramid-nylon composite blended cloth, wherein the aramid-nylon composite blended cloth is woven with nylon fibers as weft yarns and aramid fibers as warp yarns, and the warp yarn directions of the two mixed fiber cloths are stacked at an angle of 90°.
[0006] Preferably, the preparation method of the mixed fiber cloth is as follows: S1: placing the aramid-nylon composite blended cloth in deionized water for ultrasonic cleaning to remove surface impurities; S2: performing a pre-impregnation treatment, and drying and curing the pre-impregnated aramid-nylon composite blended cloth; S3: performing a secondary impregnation treatment, and drying and curing the secondary impregnated aramid-nylon composite blended cloth to obtain the mixed fiber cloth.
[0007] Preferably, the pre-impregnation treatment liquid comprises epoxy resin, blocked isocyanate and deionized water in a mass ratio of 1:5.34:66.3; the preparation method of the pre-impregnation treatment liquid is: adding the epoxy resin, blocked isocyanate and deionized water into a container in proportion, placing it in a constant temperature water bath at 30°C, and stirring at 400r / min for 1.5-2h to obtain the pre-impregnation treatment liquid.
[0008] Preferably, the secondary impregnation liquid comprises resorcinol, sodium hydroxide, deionized water, formaldehyde and butylpyrrolidone latex in a mass ratio of 35.7:1:1000:42.3:812; the preparation method of the secondary impregnation liquid is as follows: add resorcinol, sodium hydroxide and four-fifths of the total mass of deionized water into a container, place in a constant temperature water bath at 25°C and stir until completely dissolved, then add formaldehyde, and continue stirring for 1.5 hours to obtain the first mixture; mix the butylpyrrolidone latex and the remaining one-fifth of the total mass of deionized water evenly, then add the first mixture, and continue stirring the reaction at 25°C for 6-7 hours to obtain the secondary impregnation liquid.
[0009] Preferably, the pre-impregnation treatment in step S2 has an immersion time of 6 minutes, and the drying and curing treatment includes two steps of baking at 80°C for 5 minutes and baking at 130°C for 25 minutes; the secondary impregnation treatment in step S3 has an immersion time of 8 minutes, and the drying and curing treatment includes two steps of baking at 90°C for 5 minutes and baking at 130°C for 30 minutes.
[0010] Preferably, the central filament is formed by a plurality of ultra-high molecular weight polyethylene fiber filament bundles, and the central filament and the secondary outer layer filaments are provided with a carbon fiber unidirectional cloth layer, and the carbon fiber unidirectional cloth layer completely covers the ultra-high molecular weight polyethylene fiber filament bundles.
[0011] Preferably, the sisal fibers and nylon fiber fibers in the outer layer are arranged alternately.
[0012] Preferably, the water-blocking layer is formed by covering a plurality of layers of water-blocking yarn.
[0013] The present invention also provides a method for preparing a corrosion-resistant high-strength steel wire rope core, and the preparation method is as follows:
[0014] Step 1, preparing inner layer yarns: taking a predetermined number of ultra-high molecular weight polyethylene fiber filaments, bundling them into a bundle, and then wrapping them with carbon fiber unidirectional cloth and hot pressing and fixing them to obtain the inner layer yarns;
[0015] Step 2, preparing the secondary outer layer wire: taking a predetermined number of steel wires and twisting them with a stranding machine, and applying oil while closing them to obtain the secondary outer layer wire;
[0016] Step 3, preparing outer layer silk: taking a predetermined number of sisal silk and nylon fiber silk and twisting them in a predetermined arrangement with a stranding machine, closing them together and pouring oil on them to obtain the outer layer silk, and before twisting, the sisal silk is immersed in oil for 5 minutes;
[0017] Step 4, preparing a water-blocking layer: wrapping and fixing a plurality of layers of water-blocking yarns around the outer layer of silk to obtain the water-blocking layer;
[0018] Step 5, preparing a high-strength protective layer: stacking and fixing two mixed fiber cloth layers, and then vulcanizing them in a vulcanizer to obtain a fiber cloth rubber composite material, and coating the fiber cloth rubber composite material on the outer layer of the water-blocking layer to obtain the high-strength protective layer.
[0019] Preferably, in step five, the vulcanization temperature is 135° C. and the vulcanization time is 50 min.
[0020] The present invention has the following beneficial effects: the present invention provides a corrosion-resistant high-strength steel wire rope core, the core is provided with a central wire, a secondary outer wire and an outer wire, the central wire is formed by a bundle of ultra-high molecular weight polyethylene fiber filaments, and the steel wire of the secondary outer wire can ensure that the core has good support while taking into account flexibility and high strength, the outer wire is composited by sisal fiber and nylon fiber, and natural fiber and synthetic fiber are used in combination, nylon fiber has high strength tensile resistance, sisal fiber has good oil storage, and can play a lubricating effect on the inside of the core; further, a high-strength protective layer is provided outside the core, which can play a good protective role on the internal structure of the core, and prevent liquid or gaseous substances such as water vapor from entering the core to corrode it, and at the same time, a mixed fiber cloth layer is provided in the high-strength protective layer, which greatly improves the strength and tensile resistance of the high-strength protective layer, thereby improving the overall strength of the core. The warp yarn directions of the two mixed fiber cloths in the protective layer are stacked at a 90° angle, which can increase the strength of the protective layer both horizontally and vertically, and improve the tensile resistance of the core. Furthermore, in order to improve the compatibility between the mixed fiber cloth layer and the rubber in the high-strength protective layer, two dipping treatments are used to improve the interfacial bonding performance between the mixed fiber cloth layer and the rubber. The mixed fiber cloth is obtained by two dipping treatments of aramid-nylon composite blended cloth. Since the surface of aramid fiber is chemically inert and has a significant difference in polarity with rubber, the interfacial bonding performance between aramid fiber and rubber is poor. In this regard, nylon fiber is introduced to form active sites. The surface contact angle of nylon fiber is low, and its high surface energy makes its surface wettability very strong, and the basic bonding value is relatively high. After pre-impregnation and secondary impregnation, its bonding value has a qualitative surge, because a large number of amide bonds in its molecular structure can react with the main component of isocyanate in the secondary impregnation solution, and also enable the secondary impregnation solution to be able to cover and penetrate each fiber in large quantities, so that the fiber-rubber bonding force is greatly improved, avoiding the delamination of the high-strength protective layer under working conditions, reducing the strength of the rope core and the stability of the wire rope. At the same time, the present invention also proposes a method for preparing a corrosion-resistant high-strength steel wire rope core, which has simple process, is easy to implement, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a structural schematic diagram of a corrosion-resistant high-strength steel wire rope core.
[0022] In the figure: 1-ultra-high molecular weight polyethylene fiber filaments, 2-carbon fiber unidirectional cloth layer, 3-steel wire, 4-sisal wire, 5-nylon fiber filaments, 6-water-blocking layer, 7-high-strength protective layer. DETAILED DESCRIPTION
[0023] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] refer to Figure 1 , this embodiment provides a corrosion-resistant high-strength steel wire 3 rope core, including a central wire, a secondary outer wire and an outer wire, the secondary outer wire spirally wraps and twists the central wire, and the outer wire spirally wraps and twists the secondary outer wire. The central wire includes a plurality of ultra-high molecular weight polyethylene fiber filaments 1, the secondary outer wire includes a plurality of steel wires 3, and the outer wire includes a plurality of sisal wires 4 and a plurality of nylon fiber wires 5, and the number ratio of the sisal wires 4 to the nylon fiber wires 5 is 1:1. The outer circumference of the outer wire is provided with a water-blocking layer 6 and a high-strength protective layer 7 in sequence, and the high-strength protective layer 7 includes a rubber layer and a mixed fiber cloth layer provided in the rubber layer, and the mixed fiber cloth layer is formed by stacking two mixed fiber cloths. The mixed fiber cloth is obtained by twice impregnating aramid-nylon composite blended cloth, and the aramid-nylon composite blended cloth is woven with nylon fiber as weft yarn and aramid fiber as warp yarn, and the warp yarn directions of the two mixed fiber cloths are stacked at an angle of 90°. The diameter of the steel wire 3 is 0.8-1.2 times the diameter of the central wire. Since the steel wire promotes the support of the rope core, excessive use of steel wire will also cause the flexibility of the rope core to decrease. Therefore, choosing the right diameter and number of steel wires has a significant impact on the support and toughness of the rope core, and can be flexibly selected according to actual demand parameters.
[0025] The preparation method of the mixed fiber cloth is as follows: S1: placing the aramid-nylon composite blended cloth in deionized water for ultrasonic cleaning to remove surface impurities; S2: performing a pre-impregnation treatment, and drying and curing the pre-impregnated aramid-nylon composite blended cloth; S3: performing a secondary impregnation treatment, and drying and curing the secondary impregnated aramid-nylon composite blended cloth to obtain the mixed fiber cloth.
[0026] The pre-impregnation treatment liquid includes epoxy resin, blocked isocyanate and deionized water in a mass ratio of 1:5.34:66.3; the preparation method of the pre-impregnation treatment liquid is: adding the epoxy resin, blocked isocyanate and deionized water into a container in proportion, placing it in a constant temperature water bath at 30°C, and stirring at 400r / min for 1.5-2h to obtain the pre-impregnation treatment liquid.
[0027] The secondary impregnation liquid comprises resorcinol, sodium hydroxide, deionized water, formaldehyde and butylpyrrolidone latex in a mass ratio of 35.7:1:1000:42.3:812; the preparation method of the secondary impregnation liquid is as follows: resorcinol, sodium hydroxide and four-fifths of the total mass of deionized water are added into a container, and stirred in a constant temperature water bath at 25°C until completely dissolved, and then formaldehyde is added, and stirring is continued for 1.5 hours to obtain a first mixture; butylpyrrolidone latex is uniformly mixed with the remaining one-fifth of the total mass of deionized water, and then the first mixture is added, and the reaction is continuously stirred at 25°C for 6-7 hours to obtain the secondary impregnation liquid.
[0028] The pre-impregnation treatment in step S2 has an immersion time of 6 minutes, and the drying and curing treatment includes two steps of baking at 80°C for 5 minutes and baking at 130°C for 25 minutes; the secondary impregnation treatment in step S3 has an immersion time of 8 minutes, and the drying and curing treatment includes two steps of baking at 90°C for 5 minutes and baking at 130°C for 30 minutes.
[0029] The central thread is formed by a bundle of a plurality of ultra-high molecular weight polyethylene fiber filaments 1, and the central thread and the secondary outer layer thread are provided with a carbon fiber unidirectional cloth layer 2, and the carbon fiber unidirectional cloth layer 2 completely covers the bundle of ultra-high molecular weight polyethylene fiber filaments 1.
[0030] The sisal fibers 4 and the nylon fiber fibers 5 are arranged alternately in the outer layer of fibers.
[0031] The water-blocking layer 6 is formed by coating a plurality of layers of water-blocking yarn. The water-blocking layer 6 can prevent water vapor from entering the rope core and corroding the internal fibers or steel wires in a high humidity environment. The number of layers of the water-blocking yarn can be set to 2-5 layers.
[0032] This embodiment also provides a method for preparing a corrosion-resistant high-strength steel wire rope core, and the preparation method is as follows:
[0033] Step 1, preparing inner layer filaments: taking a predetermined number of ultra-high molecular weight polyethylene fiber filaments 1, bundling them into a bundle, wrapping them with carbon fiber unidirectional cloth, and hot-pressing and fixing them to obtain the inner layer filaments;
[0034] Step 2, preparing the secondary outer layer wire: taking a predetermined number of steel wires 3 and twisting them with a stranding machine, and applying oil while closing them to obtain the secondary outer layer wire;
[0035] Step 3, preparing outer layer silk: taking a predetermined number of sisal silk 4 and nylon fiber silk 5 and twisting them in a predetermined arrangement using a stranding machine, closing them together and pouring oil on them to obtain the outer layer silk, and before twisting, the sisal silk 4 is immersed in oil for 5 minutes;
[0036] Step 4, preparing a water-blocking layer: wrapping and fixing 2-3 layers of water-blocking yarn around the outer layer of silk to obtain the water-blocking layer 6;
[0037] Step 5, preparing a high-strength protective layer: stack and fix two mixed fiber cloths, and then vulcanize them in a vulcanizer to obtain a fiber cloth rubber composite material, and wrap the fiber cloth rubber composite material on the outer layer of the water-blocking layer 6 to obtain the high-strength protective layer 7.
[0038] Wherein, in step 5, the vulcanization temperature is 135° C. and the vulcanization time is 50 min.
[0039] Example 1
[0040] This embodiment provides a corrosion-resistant high-strength steel wire rope core, and the preparation steps are as follows:
[0041] Step 1, preparing inner layer wires: taking a predetermined number of ultra-high molecular weight polyethylene fiber filaments, bundling them into a bundle, wrapping them with carbon fiber unidirectional cloth, and hot pressing and fixing them to obtain the inner layer wires, wherein the inner layer wires have a diameter of 1 mm;
[0042] Step 2, preparing the secondary outer layer wire: taking a predetermined number of steel wires and twisting them with a stranding machine, and applying oil while closing them to obtain the secondary outer layer wire, wherein the diameter of the steel wire is 0.8 mm;
[0043] Step 3, preparing outer layer yarn: taking a predetermined number of sisal yarns and nylon fiber yarns and twisting them with a stranding machine in a predetermined arrangement, closing them together and pouring oil on them to obtain outer layer yarns, and soaking the sisal yarns in oil for 5 minutes before twisting, and obtaining a yarn with a diameter of 8 mm after twisting;
[0044] Step 4, preparing a water-blocking layer: wrapping and fixing three layers of water-blocking yarn on the periphery of the outer layer of silk to obtain the water-blocking layer;
[0045] Step 5, preparing a high-strength protective layer: stack and fix two mixed fiber cloths at a 90° angle in the warp direction, and then vulcanize them in a vulcanizer to obtain a fiber cloth rubber composite material. The vulcanization temperature is 135°C and the vulcanization time is 50 minutes. The fiber cloth rubber composite material is coated on the outer layer of the water-blocking layer to obtain the high-strength protective layer. The thickness of the high-strength protective layer is 0.8 mm.
[0046] The preparation method of the mixed fiber cloth is:
[0047] S1: The aramid-nylon composite blended fabric is placed in deionized water for ultrasonic cleaning to remove surface debris;
[0048] S2: Pre-impregnation treatment is carried out using a dipping machine, the pre-impregnation treatment time is 6 minutes, and the aramid-nylon composite blended fabric after pre-impregnation treatment is dried and cured, and the drying and curing treatment is first baked at 80°C for 5 minutes, and then baked at 130°C for 25 minutes; the preparation steps of the pre-impregnation treatment liquid: weigh epoxy resin, blocked isocyanate and deionized water in a mass ratio of 1:5.34:66.3, add them into a container, keep a constant temperature water bath at 30°C, and stir at 400r / min for 1.5h to obtain.
[0049] S3: A dipping machine is used for secondary dipping treatment, the secondary dipping treatment time is 8 minutes, and the aramid-nylon composite blended fabric subjected to secondary dipping treatment is dried and solidified to obtain the mixed fiber fabric. The drying and solidification treatment is first dried at 90°C for 5 minutes, and then dried at 130°C for 30 minutes to obtain the mixed fiber fabric; the secondary dipping treatment liquid preparation steps are as follows: prepare resorcinol, sodium hydroxide, deionized water, formaldehyde and butylpyrrolidone latex in a mass ratio of 35.7:1:1000:42.3:812, add resorcinol, sodium hydroxide and four-fifths of the total mass of deionized water into a container, place in a constant temperature water bath at 25°C and stir until completely dissolved, then add formaldehyde, and continue stirring for 1.5 hours to obtain the first mixture; mix the butylpyrrolidone latex and the remaining one-fifth of the total mass of deionized water evenly, then add the first mixture, and continue stirring and reacting at 25°C for 6 hours to obtain the secondary dipping solution.
[0050] Example 2
[0051] This embodiment provides a corrosion-resistant high-strength steel wire rope core, and the preparation steps are as follows:
[0052] Step 1, preparing inner layer wires: taking a predetermined number of ultra-high molecular weight polyethylene fiber filaments, bundling them into a bundle, wrapping them with carbon fiber unidirectional cloth, and hot pressing and fixing them to obtain the inner layer wires, wherein the inner layer wires have a diameter of 1 mm;
[0053] Step 2, preparing outer layer silk: taking a predetermined number of sisal silk and nylon fiber silk and twisting them in a predetermined arrangement with a stranding machine, closing them together and pouring oil on them to obtain outer layer silk, and before twisting, the sisal silk is soaked in oil for 5 minutes, and after twisting, the diameter is 8 mm;
[0054] Step 3, preparing a water-blocking layer: wrapping and fixing three layers of water-blocking yarn on the periphery of the outer layer of silk to obtain the water-blocking layer;
[0055] Step 4, prepare a high-strength protective layer: stack and fix two mixed fiber cloths at a 90° angle in the warp direction, and then vulcanize them in a vulcanizer to obtain a fiber cloth rubber composite material. The vulcanization temperature is 135°C and the vulcanization time is 50 minutes. The fiber cloth rubber composite material is coated on the outer layer of the water-blocking layer to obtain the high-strength protective layer. The thickness of the high-strength protective layer is 0.8 mm.
[0056] The preparation method of the mixed fiber cloth is:
[0057] S1: The aramid-nylon composite blended fabric is placed in deionized water for ultrasonic cleaning to remove surface debris;
[0058] S2: Pre-impregnation treatment is carried out using a dipping machine, the pre-impregnation treatment time is 6 minutes, and the aramid-nylon composite blended fabric after pre-impregnation treatment is dried and cured, and the drying and curing treatment is first baked at 80°C for 5 minutes, and then baked at 130°C for 25 minutes; the preparation steps of the pre-impregnation treatment liquid: weigh epoxy resin, blocked isocyanate and deionized water in a mass ratio of 1:5.34:66.3, add them into a container, keep a constant temperature water bath at 30°C, and stir at 400r / min for 1.5h to obtain.
[0059] S3: A dipping machine is used for secondary dipping treatment, the secondary dipping treatment time is 8 minutes, and the aramid-nylon composite blended fabric subjected to secondary dipping treatment is dried and solidified to obtain the mixed fiber fabric. The drying and solidification treatment is first dried at 90°C for 5 minutes, and then dried at 130°C for 30 minutes to obtain the mixed fiber fabric; the secondary dipping treatment liquid preparation steps are as follows: prepare resorcinol, sodium hydroxide, deionized water, formaldehyde and butylpyrrolidone latex in a mass ratio of 35.7:1:1000:42.3:812, add resorcinol, sodium hydroxide and four-fifths of the total mass of deionized water into a container, place in a constant temperature water bath at 25°C and stir until completely dissolved, then add formaldehyde, and continue stirring for 1.5 hours to obtain the first mixture; mix the butylpyrrolidone latex and the remaining one-fifth of the total mass of deionized water evenly, then add the first mixture, and continue stirring and reacting at 25°C for 6 hours to obtain the secondary dipping solution.
[0060] Example 3
[0061] This embodiment provides a corrosion-resistant high-strength steel wire rope core, and the preparation steps are as follows:
[0062] Step 1, preparing inner layer wires: taking a predetermined number of ultra-high molecular weight polyethylene fiber filaments, bundling them into a bundle, wrapping them with carbon fiber unidirectional cloth, and hot pressing and fixing them to obtain the inner layer wires, wherein the inner layer wires have a diameter of 1 mm;
[0063] Step 2, preparing the secondary outer layer wire: taking a predetermined number of steel wires and twisting them with a stranding machine, and applying oil while closing them to obtain the secondary outer layer wire, wherein the diameter of the steel wire is 0.8 mm;
[0064] Step 3, preparing outer layer yarn: taking a predetermined number of sisal yarns and nylon fiber yarns and twisting them with a stranding machine in a predetermined arrangement, closing them together and pouring oil on them to obtain outer layer yarns, and soaking the sisal yarns in oil for 5 minutes before twisting, and obtaining a yarn with a diameter of 8 mm after twisting;
[0065] Step 4, preparing a water-blocking layer: wrapping and fixing three layers of water-blocking yarn on the periphery of the outer layer of silk to obtain the water-blocking layer;
[0066] Step 5, preparing a high-strength protective layer: take a mixed fiber cloth and vulcanize it in a vulcanizer to obtain a fiber cloth rubber composite material, the vulcanization temperature is 135°C, the vulcanization time is 50 minutes, and the fiber cloth rubber composite material is coated on the outer layer of the water-blocking layer to obtain the high-strength protective layer, and the thickness of the high-strength protective layer is 0.8 mm.
[0067] The preparation method of the mixed fiber cloth is:
[0068] S1: The aramid-nylon composite blended fabric is placed in deionized water for ultrasonic cleaning to remove surface debris;
[0069] S2: Pre-impregnation treatment is carried out using a dipping machine, the pre-impregnation treatment time is 6 minutes, and the aramid-nylon composite blended fabric after pre-impregnation treatment is dried and cured, and the drying and curing treatment is first baked at 80°C for 5 minutes, and then baked at 130°C for 25 minutes; the preparation steps of the pre-impregnation treatment liquid: weigh epoxy resin, blocked isocyanate and deionized water in a mass ratio of 1:5.34:66.3, add them into a container, keep a constant temperature water bath at 30°C, and stir at 400r / min for 1.5h to obtain.
[0070] S3: A dipping machine is used for secondary dipping treatment, the secondary dipping treatment time is 8 minutes, and the aramid-nylon composite blended fabric subjected to secondary dipping treatment is dried and solidified to obtain the mixed fiber fabric. The drying and solidification treatment is first dried at 90°C for 5 minutes, and then dried at 130°C for 30 minutes to obtain the mixed fiber fabric; the secondary dipping treatment liquid preparation steps are as follows: prepare resorcinol, sodium hydroxide, deionized water, formaldehyde and butylpyrrolidone latex in a mass ratio of 35.7:1:1000:42.3:812, add resorcinol, sodium hydroxide and four-fifths of the total mass of deionized water into a container, place in a constant temperature water bath at 25°C and stir until completely dissolved, then add formaldehyde, and continue stirring for 1.5 hours to obtain the first mixture; mix the butylpyrrolidone latex and the remaining one-fifth of the total mass of deionized water evenly, then add the first mixture, and continue stirring and reacting at 25°C for 6 hours to obtain the secondary dipping solution.
[0071] Example 4
[0072] This embodiment provides a corrosion-resistant high-strength steel wire rope core, and the preparation steps are as follows:
[0073] Step 1, preparing inner layer wires: taking a predetermined number of ultra-high molecular weight polyethylene fiber filaments, bundling them into a bundle, wrapping them with carbon fiber unidirectional cloth, and hot pressing and fixing them to obtain the inner layer wires, wherein the inner layer wires have a diameter of 1 mm;
[0074] Step 2, preparing the secondary outer layer wire: taking a predetermined number of steel wires and twisting them with a stranding machine, and applying oil while closing them to obtain the secondary outer layer wire, wherein the diameter of the steel wire is 0.8 mm;
[0075] Step 3, preparing outer layer yarn: taking a predetermined number of sisal yarns and nylon fiber yarns and twisting them with a stranding machine in a predetermined arrangement, closing them together and pouring oil on them to obtain outer layer yarns, and soaking the sisal yarns in oil for 5 minutes before twisting, and obtaining a yarn with a diameter of 8 mm after twisting;
[0076] Step 4, preparing a water-blocking layer: wrapping and fixing three layers of water-blocking yarn on the periphery of the outer layer of silk to obtain the water-blocking layer;
[0077] Step 5, preparing a high-strength protective layer: stack and fix two mixed fiber cloths at a 90° angle in the warp direction, and then vulcanize them in a vulcanizer to obtain a fiber cloth rubber composite material. The vulcanization temperature is 135°C and the vulcanization time is 50 minutes. The fiber cloth rubber composite material is coated on the outer layer of the water-blocking layer to obtain the high-strength protective layer. The thickness of the high-strength protective layer is 0.8 mm.
[0078] The preparation method of the mixed fiber cloth is:
[0079] S1: The aramid-nylon composite blended fabric is placed in deionized water for ultrasonic cleaning to remove surface debris;
[0080] S2: Pre-impregnation treatment is carried out by using a dipping machine, the pre-impregnation treatment time is 6 minutes, and the aramid-nylon composite blended fabric after pre-impregnation treatment is dried and cured. The drying and curing treatment is first baked at 80°C for 5 minutes, and then baked at 130°C for 25 minutes to obtain a mixed fiber cloth; the preparation step of the pre-impregnation treatment liquid: weigh epoxy resin, blocked isocyanate and deionized water in a mass ratio of 1:5.34:66.3, add them into a container, keep a constant temperature water bath at 30°C, and stir at 400r / min for 1.5h to obtain.
[0081] Comparative Example 1
[0082] This comparative example provides a steel wire rope core. Compared with the corrosion-resistant high-strength steel wire rope core provided in Example 1, the difference between the steel wire rope core and the corrosion-resistant high-strength steel wire rope core is that the outer periphery of the outer layer of the steel wire rope core is not provided with a water-blocking layer and a high-strength protective layer, and the preparation step also omits the preparation of the water-blocking layer and the high-strength protective layer.
[0083] The steel wires twisted on the outer circumference of the steel wire rope core prepared in Examples 1-4 and Comparative Example 1 were made into steel wire ropes with a diameter of 16 mm, and the performance of the steel wire ropes was tested in accordance with the national standard GB / T 17107-2008. The steel wire ropes were placed in an acid mist environment with a mass fraction of 10% hydrochloric acid at a temperature of 25°C for 24 hours, and the corrosion degree of the steel wire inside the steel wire rope core was observed under a microscope. The test results are shown in Table 1 below.
[0084] Table 1
[0085]
[0086] From the above data, it can be seen that the corrosion-resistant high-strength steel wire rope core proposed by the present invention has high strength and high stability, and has a promoting effect on improving the breaking force of the steel wire rope. The rope core can well prevent water vapor and other corrosive gases from entering the rope core by setting a water-blocking layer and a high-strength protective layer, thereby ensuring the stability and strength of the internal structure of the rope core. From the data of Examples 1 and 4, it can be seen that the use of two impregnations can increase the bonding force between the mixed fiber cloth and the rubber, thereby improving the strength of the steel wire rope.
[0087] The present invention is described in detail above in conjunction with the embodiments. It should be noted that the various specific technical features described in the above specific embodiments can be combined and changed in any suitable manner without contradiction, and the present invention will not further describe various possible combinations. In addition, other variations and combinations of the various technical features of the present invention should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A corrosion-resistant high-strength steel wire rope core, comprising a central wire, a secondary outer wire and an outer wire, wherein the secondary outer wire is spirally wrapped around the central wire, and the outer wire is spirally wrapped around the secondary outer wire, characterized in that: The central wire includes a plurality of ultra-high molecular weight polyethylene fiber filaments, the secondary outer layer wire includes a plurality of steel wires, the outer layer wire includes a plurality of sisal wires and a plurality of nylon fiber wires, and the quantity ratio of the sisal wires to the nylon fiber wires is 1:1; the outer layer wire is provided with a water-blocking layer and a high-strength protective layer in sequence on the periphery, the high-strength protective layer includes a rubber layer and a mixed fiber cloth layer arranged in the rubber layer, and the mixed fiber cloth layer is formed by stacking two mixed fiber cloths; the mixed fiber cloth is obtained by twice impregnating an aramid-nylon composite blended cloth, and the aramid-nylon composite blended cloth is woven with nylon fiber as weft yarn and aramid fiber as warp yarn, and the warp yarn directions of the two mixed fiber cloths are stacked at an angle of 90°.
2. The corrosion-resistant high-strength steel wire rope core according to claim 1, characterized in that: The preparation method of the mixed fiber cloth is as follows: S1: placing the aramid-nylon composite blended cloth in deionized water for ultrasonic cleaning to remove surface impurities; S2: performing a pre-impregnation treatment, and drying and curing the pre-impregnated aramid-nylon composite blended fabric; S3: performing a secondary impregnation treatment, and drying and curing the secondary impregnated aramid-nylon composite blended fabric to obtain the mixed fiber fabric.
3. The corrosion-resistant high-strength steel wire rope core according to claim 2, characterized in that: The pre-impregnation treatment liquid includes epoxy resin, blocked isocyanate and deionized water in a mass ratio of 1:5.34:66.3; the preparation method of the pre-impregnation treatment liquid is: adding the epoxy resin, blocked isocyanate and deionized water into a container in proportion, placing it in a constant temperature water bath at 30°C, and stirring at 400r / min for 1.5-2h to obtain the pre-impregnation treatment liquid.
4. The corrosion-resistant high-strength steel wire rope core according to claim 3, characterized in that: The secondary impregnation liquid comprises resorcinol, sodium hydroxide, deionized water, formaldehyde and butylpyrrolidone latex in a mass ratio of 35.7:1:1000:42.3:812; the preparation method of the secondary impregnation liquid is as follows: resorcinol, sodium hydroxide and four-fifths of the total mass of deionized water are added into a container, and stirred in a constant temperature water bath at 25°C until completely dissolved, and then formaldehyde is added, and stirring is continued for 1.5 hours to obtain a first mixture; butylpyrrolidone latex is uniformly mixed with the remaining one-fifth of the total mass of deionized water, and then the first mixture is added, and the reaction is continuously stirred at 25°C for 6-7 hours to obtain the secondary impregnation liquid.
5. The corrosion-resistant high-strength steel wire rope core according to claim 2, characterized in that: The pre-impregnation treatment in step S2 has an immersion time of 6 minutes, and the drying and curing treatment includes two steps of baking at 80°C for 5 minutes and baking at 130°C for 25 minutes; the secondary impregnation treatment in step S3 has an immersion time of 8 minutes, and the drying and curing treatment includes two steps of baking at 90°C for 5 minutes and baking at 130°C for 30 minutes.
6. The corrosion-resistant high-strength steel wire rope core according to claim 1, characterized in that: The central thread is formed by a plurality of ultra-high molecular weight polyethylene fiber filament bundles, and the central thread and the secondary outer layer thread are provided with a carbon fiber unidirectional cloth layer, and the carbon fiber unidirectional cloth layer completely covers the ultra-high molecular weight polyethylene fiber filament bundles.
7. The corrosion-resistant high-strength steel wire rope core according to claim 1, characterized in that: The sisal fibers and the nylon fiber fibers in the outer layer are arranged alternately and at intervals.
8. The corrosion-resistant high-strength steel wire rope core according to claim 7, characterized in that: The water-blocking layer is formed by covering a plurality of layers of water-blocking yarns.
9. A method for preparing a corrosion-resistant high-strength steel wire rope core, used for preparing the corrosion-resistant high-strength steel wire rope core as claimed in any one of claims 1 to 8, characterized in that: The preparation method is as follows: Step 1, preparing inner layer yarns: taking a predetermined number of ultra-high molecular weight polyethylene fiber filaments, bundling them into a bundle, and then wrapping them with carbon fiber unidirectional cloth and hot pressing and fixing them to obtain the inner layer yarns; Step 2, preparing the secondary outer layer wire: taking a predetermined number of steel wires and twisting them with a stranding machine, and applying oil while closing them to obtain the secondary outer layer wire; Step 3, preparing outer layer silk: taking a predetermined number of sisal silk and nylon fiber silk and twisting them in a predetermined arrangement with a stranding machine, closing them together and pouring oil on them to obtain the outer layer silk, and before twisting, the sisal silk is immersed in oil for 5 minutes; Step 4, preparing a water-blocking layer: wrapping and fixing a plurality of layers of water-blocking yarns around the outer layer of silk to obtain the water-blocking layer; Step 5, preparing a high-strength protective layer: stacking and fixing two mixed fiber cloth layers, and then vulcanizing them in a vulcanizer to obtain a fiber cloth rubber composite material, and coating the fiber cloth rubber composite material on the outer layer of the water-blocking layer to obtain the high-strength protective layer.
10. The method for preparing the corrosion-resistant high-strength steel wire rope core according to claim 9, characterized in that: In step 5, the vulcanization temperature is 135° C. and the vulcanization time is 50 min.
Citation Information
Patent Citations
High-strength steel wire rope core and preparation method thereof
CN116446203A
Elevator steel wire rope
CN117005223A
Steel wire rope with high polymer material rope core
CN215668714U
Steel wire rope for ocean engineering
CN217479826U
Pneumatic tire, its manufacturing method, rubber product and its manufacturing method
JP2007245811A